Rational tuning of high-energy visible light absorption for panchromatic small molecules by a two-dimensional conjugation approach. Issue 6 (7th March 2016) - He, Bo; Zherebetskyy, Danylo; Wang, Hongxia; Kolaczkowski, Matthew A.; Klivansky, Liana M.; Tan, Tianwei; Wang, Linwang; Liu, Yi
Abstract : Rational design leads to panchromatic absorption in small molecules by extension of conjugation on two orthogonal axes of an indigo-derived electron acceptor. Abstract : We have demonstrated a rational two-dimensional (2D) conjugation approach towards achieving panchromatic absorption of small molecules. By extending the conjugation on two orthogonal axes of an electron acceptor, namely, bay-annulated indigo (BAI ), the optical absorptions could be tuned independently in both high- and low-energy regions. The unconventional modulation of the high-energy absorption is rationalized by density functional theory (DFT) calculations. Such a 2D tuning strategy provides novel guidelines for the design of molecular materials with tailored optoelectronic properties.